Competitive locations of grocery stores in the local supply context – The case of the urban district Freiburg-Haslach - Thomas WIELAND (European Journal of Geography)
The local supply function of grocery stores is threatened in rural areas as well as in urban districts. While “sufficient” or “qualified” local supply is defined normatively in terms of store accessibility and variety, the underlying assumptions on consumer behavior are not underpinned empirically. This article discusses the theoretical basics of spatial competition in grocery retailing from the perspective of retail location theory. The deduced assumptions on store choice are tested empirically regarding grocery stores in an urban district (FreiburgHaslach), using an extended version of the Multiplicative Competitive Interaction (MCI) Model. As assumed by location theory and discussed in the local supply context, the most important aspect is store accessibility, which is operationalized in several ways. While store size has a positive impact, no clear results towards pricing can be found. There is empirical evidence on positive agglomeration effects with respect to different store formats.